Perbedaan Cara Menjawab Pertanyaan Antara Mahasiswa Laki-Laki Dan Perempuan Dengan Menggunakan Konsep R3Mr - Suryawahyuni Latief (STIT Muhammadiyah Paciran Lamongan, 2020)
Abstract: The main purpose of this study is to know about thedifferences between gender and style of answer the question ofundergraduate students in V semester of Government Science field,Syariah Faculty, UIN Sulthan Thaha Syaifuddin, Jambi, 2018/2019academic year. This study employed statistic descriptive analyze bychi-square and determined four variable, named R3Mr. The studyfound that there is a difference between gender and style of answerquestion, which is male students dominated in R1 and Mr variable, thepercentage of R1 and Mr variable are 70.7% and 62.5%, while thefemale students are in R2 and R3 variable, that is 62.5% and 53.3%